The Structure, Function, and Origin of the Microcin H47 ATP-Binding Cassette Exporter Indicate Its Relatedness to That of Colicin V - Azpiroz, María F. (American Society for Microbiology, 2001)
Microcin H47, a gene-encoded peptide antibiotic produced by a natural Escherichia coli strain, was shown to be secreted by a three-component ATP-binding cassette exporter which was revealed to be strongly related to that of colicin V. The results of sequence and gene fusion analyses, as well as heterologous complementation assays, are presented.